Display Space Usage and Window Management Operation Comparisons Between Single Monitor and Multiple Monitor Users - Hutchings, Dugald; Smith, Greg; Meyers, Brian; Czerwinski, Mary; Robertson, George (Advanced Visual Interfaces 2004, 2004)
The continuing trend toward greater processing power, larger storage, and in particular increased display surface by using multiple monitor supports increased multi-tasking by the computer user. The concomitant increase in desktop complexity has the potential to push the overhead of window management to frustrating and counterproductive new levels. It is difficult to adequately design for multiple monitor systems without understanding how multiple monitor users differ from, or are similar to, single monitor users. Therefore, we deployed a tool to a group of single monitor and multiple monitor users to log window management activity. Analysis of the data collected from this tool revealed that usage of interaction components may change with an increase in number of monitors, and window visibility can be a useful measure of user display space management activity, especially for multiple monitor users. The results from this analysis begin to fill a gap in research about real-world window management practices.